Pengembangan Buku Pengayaan Kajian Fisis Peristiwa Angin Puting Beliung untuk Siswa SMA - Desnita Desnita; Noviana Fadilah; Esmar Budi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2016)
Abstract This research is aimed to develop knowledge enrichment book about tornado as a physics learning resource, especially to Bassed Competence 3.7 Class XI, namely Applying the principle of fluid dynamics in technology. The method applied in this research is the Development Research referring to the Dick and Carey model. Steps that was done are survey in eight high school, two well-known bookstore in Jakarta, online bookstore, and Pusat Kurikulum dan Perbukuan (Puskurbuk). The survey results show there is knowledge enrichment book is presented with more focus on the disaster that is less scientific and less deep because only limited discuss section. Referring to the results of the survey and quality standards enrichment books, knowledge enrichment book is written by discuss mainly the physical quantities of gas flow especially pressure gradient, the events and the physical concept of tornado, to disaster mitigation. Based on results of the readability test to high school students is obtained a mean score of materials component is 92,5%, 88,5% for presentation, 84,17% for language, and 85,62% for graphics. Score 87,5% stated that the material in the book is easy to understand and 82,5% stated that the presentation materials may be motivated to dig up more information. Based on results of readability test, thin book obtaine excellent overall interpretation. Based on the results of the feasibility test, gets an average score of 81,05, showing knowledge enrichment book